Successful Treatment with Taxane-Based Chemotherapy in Advanced Sebaceous Carcinoma: A Case Report and Literature Review - Shuji Ota (Case Reports in Oncology, 2019)
For sebaceous carcinoma (SC), a rare malignant tumor, no standard chemotherapy regimen for patients with distant metastasis has been studied. We experienced a case of eyelid SC with multiple lung metastases that responded to combination chemotherapy with carboplatin and paclitaxel with 11-month progression-free survival (PFS). This patient also responded to second-line treatment with docetaxel, another taxane, with 7-month PFS, resulting in at least 18 months of survival at the time of reporting. This report shows that taxane-based chemotherapy may be effective for advanced SC, for which no standard therapy has been established.